Magnetic phase diagram of the infinite- U Hubbard model with nearest- and next-nearest-neighbor hoppings - Blesio, Germán Gabriel (2019)
We study the infinite-U Hubbard model on ladders of two, four, and six legs with nearest- (t) and next-nearest- (t′) neighbor hoppings by means of the density-matrix renormalization group algorithm. In particular, we analyze the stability of the Nagaoka state for several values of t′ when we vary the electron density ρ from half filling to the low-density limit. We build the two-dimensional phase diagram, where the fully spin polarized and paramagnetic states prevail. We find that the inclusion of a nonfrustrating next-nearest-neighbor hopping stabilizes the fully spin polarized phase up until |t′/t|=0.5. Surprisingly, for this value of t′, the ground state is fully spin polarized for almost any electron density 1 ρ 0, connecting the Nagaoka state to itinerant ferromagnetism at low density. Also, we find that the previously found checkerboard insulator phase at t′=0 and ρ=0.75 is unstable against t′.